Analysing the Effects of Unethical Culture and Organizational Commitment on Employees' and Managers' Unethical Behaviours: Evidence from Turkish Insurance Industry - Karabay, Melisa Erdilek; Elci, Meral; Akpinar, Ozgur (Springer-Verlag Singapore Pte Ltd, 2018)
[No abstract available]
Keywords: Ethical Behavior; Business Ethics; Moral Development; Job-Satisfaction; Values; Intention; Climates; Conduct; Impact; Codes